Hexabromocyclododecanes (HBCDs) in fish: Evidence of recent HBCD input into the coastal environment. (January 2018) - Sun, Runxia; Luo, Xiaojun; Zheng, Xiaobo; Cao, Kun; Peng, Pingan; Li, Qing X.; Mai, Bixian
Abstract: Hexabromocyclododecanes (HBCDs) are flame retardants and emerging persistent organic pollutants. In the present study, α-, β-, and γ-HBCDs were measured in several fish species from rivers and an electronic waste (e-waste) recycling site in Pearl River Delta, South China. The concentrations of HBCDs were 12.8 to 640, 5.90 to 115, and 34.3 to 518 ng/g lipid weight (lw) in mud carp ( Cirrhinus molitorella ), tilapia ( Tilapia nilotica ), and plecostomus ( Hypostomus plecostomus ), respectively. Plecostomus showed the highest HBCD concentrations among three fish species. The contributions of α-HBCD to total HBCDs were 78% to 97%, 93% to 99%, and 87% to 98% in carp, tilapia, and plecostomus, respectively. Fish samples from a harbor and the e-waste site exhibited the highest HBCD concentrations among all samples. The HBCD concentrations were not significantly correlated with the gross domestic product or population data. e-Waste recycling activities, harbor construction, and shipment might be recent HBCD sources. Highlights: HBCDs were measured in three fish species from the PRD region. Plecostomus had significantly higher HBCD levels than mud carp and tilapia. Highest HBCD levels were founded in fish from the e-waste site and a harbor. HBCD concentrations were not correlated with population and GDP data.